Lipid and Protein Oxidation in Newborn Infants after Lutein Administration. (11th May 2014) - Perrone, S.; Tei, M.; Longini, M.; Santacroce, A.; Turrisi, G.; Proietti, F.; Felici, C.; Picardi, A.; Bazzini, F.; Vasarri, P.; Buonocore, G.
Abstract : Objectives . To test the hypothesis that neonatal supplementation with lutein in the first hours of life reduces neonatal oxidative stress (OS) in the immediate postpartum period. Methods . A randomized controlled, double-blinded clinical trial was conducted among 150 newborns divided into control group, not supplemented (n = 47 ), and test group, supplemented with lutein on the first day postpartum (n = 103 ). Blood Samples were collected at birth from cord and at 48 hrs postpartum while routine neonatal metabolic screenings were taking place. Total hydroperoxide (TH), advanced oxidation protein products (AOPP), and biological antioxidant potential (BAP) were measured by spectrophotometry and data were analyzed by Wilcoxon rank sum test and by multivariate logistic regression analysis. Results . Before lutein supplementation, the mean blood concentrations of AOPP, TH, and BAP were 36.10 umol/L, 156.75 mmol/H2 O2, and 2361.04 umol/L in the test group. After lutein supplementation, significantly higher BAP increment (0.17 ± 0.22 versus 0.06 versus ± 0.46) and lower TH increment (0.46 ± 0.54 versus 0.34 ± 0.52) were observed in the test group compared to controls. Conclusion . Neonatal supplementation with lutein in the first hours of life increases BAP and reduces TH in supplemented babies compared to those untreated. The generation of free radical-induced damage at birth is reduced by lutein. This trial is registered with ClinicalTrials.gov NCT02068807 .